ISOLASI METABOLIT SEKUNDER DAN UJI TOKSISITAS EKSTRAK METANOL DAGING BUAH TANAMAN Cerbera odollam Gaertn. (APOCYNACEAE) - Nelma Yeni; Hilwan Yuda Teruna; Jasril ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Cerbera odollam Gaertn is a plant found in Indonesia which is used as traditional medicine. Isolation and toxicity assay on fruit flesh of this plant has been done. The methanol macerating method was applied to isolate the secondary metabolites from part of this plant. The separation was carried out by vacuum liquid chromatography (VLC), gel chromatography and KLT preparative. Characterization of the fractions was established using UV-Vis and FTIR spectroscopy. Toxicity assay was conducted by Brine Shrimp Lethality Test (BSLT) method. The LC50 of 7th to 11th fractions of the methanol extract were 107,86 ; 5,19; 136,42 ; 41,33 and 720,60 ppm, respectively. The 5th and 6th fractions were not toxic, the 11th fraction was toxic whereas other fractions were very toxic and potential to be used as an anticancer.